A comprehensive thermodynamic and exergoeconomic comparison between single- and two-stage thermoelectric cooler and heater. (September 2017) - Nami, Hossein; Nemati, Arash; Yari, Mortaza; Ranjbar, Faramarz
Highlights: Single- and two-stage thermoelectric devices are used as heater and cooler. The exergoeconomic analysis is adopted for the thermoelectric devices. A comprehensive comparison has been done between single- and two-stage thermoelectrics. An effective rage of current is defined for energy, exergy and exergoeconomic analysis. Single-stage thermoelectric performs better than two-stage one exergoeconomically. Abstract: Energy, exergy and exergoeconomic analysis are carried out for single- and two-stage thermoelectric devices which can be used for either heating or cooling implementation. Coefficient of performance, exergetic efficiency and unit cost of heating/cooling power are investigated as the main target of energy, exergy and exergoeconomic analysis, respectively. A comprehensive comparison between single- and two-stage thermoelectric performances has outlined in different values of current and temperature difference between hot and cold sides. An effective range of current is defined for energy (COP > 0.5 × COPmax ), exergy (ε > 0.5 × εmax ) and exergoeconomic (cC/H < 2 × cC/H, min ) analysis. Thermodynamic analysis results reveal that the maximized energy and exergy efficiency of two-stage thermoelectric is higher in comparison to the single-stage thermoelectric for both heating and cooling modes. Also, based on exergoeconomic results, minimum unit cost of single-stage thermoelectric product is less than that of two-stage thermoelectric for all temperature differences and effective range of current is more widespread for the case of single-stage thermoelectric. Obtained results reveal that the minimum unit cost of cooling power for single- and two-stage cooler is 3.967 and 16.22 /kW h, respectively, for temperature difference of 10 K.